Chemodivergent photocatalytic access to 1-pyrrolines and 1-tetralones involving switchable C(sp3)–H functionalization - Tu, Shijing; Qi, Zhongyu; Li, Weicai; Zhang, Shiqi; Zhang, Zhijie; Wei, Jun; Yang, Lin; Wei, Siping; Du, Xi; Yi, Dong (Frontiers in Chemistry, 2022)
A chemodivergent photocatalytic approach to 1-pyrrolines and 1-tetralones from alkyl bromides and vinyl azides has been developed through chemoselectively controllable intermolecular [3+2] and [4+2] cyclization. This photoredox-neutral two-component protocol involves intermolecular radical addition and switchable distal C(sp3)–H functionalization enabled by iminyl radical-mediated 1,5-hydrogen atom transfer. Meanwhile, chemoselectivity between C(sp3)–N bond formation and C(sp3)–C(sp2) bond formation is precisely switched by photocatalysts (Ru(bpy)3(PF6)2 vs. fac-Ir(ppy)3) and additives (base vs. acid).